2018
DOI: 10.1007/s00384-018-3033-7
|View full text |Cite
|
Sign up to set email alerts
|

Do clinical criteria reflect pathologic complete response in rectal cancer following neoadjuvant therapy?

Abstract: Most patients undergoing neoadjuvant therapy for rectal cancer have residual mucosal abnormalities which preclude to a cCR as per published criteria from Brazil. Further studies are required to optimize clinical evaluation and MRI imaging in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…The following 3 criteria were required to achieve cCR: no mass remaining upon rectoscopic examination, soft palpation on the digital exam, and absence of residual tumor on MRI [ 23 ]. If there was interval regression on two consecutive endoscopic evaluations, small soft ulcers were considered acceptable “near complete response” [ 16 , 24 , 25 ] and eligible for continued surveillance. However, if the 3 criteria specified above were not fulfilled, patients were characterized as non-complete clinical responders.…”
Section: Methodsmentioning
confidence: 99%
“…The following 3 criteria were required to achieve cCR: no mass remaining upon rectoscopic examination, soft palpation on the digital exam, and absence of residual tumor on MRI [ 23 ]. If there was interval regression on two consecutive endoscopic evaluations, small soft ulcers were considered acceptable “near complete response” [ 16 , 24 , 25 ] and eligible for continued surveillance. However, if the 3 criteria specified above were not fulfilled, patients were characterized as non-complete clinical responders.…”
Section: Methodsmentioning
confidence: 99%
“…11 In line with our findings, several studies demonstrated that some patients with residual mucosal abnormalities, therefore regarded as incomplete clinical responders, may have achieved pCR. [13][14][15][16] Accordingly, it is hypothesized that the majority of patients with pCR does not have the mucosal features displaying a cCR. In other words, an incomplete clinical response due to residual mucosal abnormalities may not be a reliable indicator of the absence of pCR.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also demonstrated that the recommended criteria for cCR is a poorly sensitive indicator of the pCR. [13][14][15][16] In a study, Smith et al determined the performance of cCR criteria. Seventyfour percent of their pCR patients had a residual mucosal abnormality (the most common abnormality being ulcer), precluding the diagnosis of a cCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…pCR may sometimes present as an incomplete response showed as mucosal ulceration, irregularities, and rectal lumen stenosis. [88][89][90] That necessitates more tools and biomarkers involved to increase the accuracy and reliability of tumor response assessment.…”
Section: Reassessmentmentioning
confidence: 99%